IMPLEMENTASI KEBIJAKAN PROGRAM KEBUN BIBIT RAKYAT (KBR) DI KECAMATAN BAMBALAMOTU KABUPATEN MAMUJU UTARA - Muin Tatro, Abdul (Katalogis, 2015)
The result of observations at research objects, the implementation of people’s nursery program policy in Bambalamotu Subdistrict, North Mamuju Regency over the last 3 years (2011 to 2013), has not shown the optimal result, therefore the aim of this research is to ascertain the the implementation of people’s nursery program policy in Bambalamotu Subdistrict, North Mamuju Regency. This is a qualitative research with descriptive method. The number of informants in this research is 7 persons, taken by purposive sampling technique. This research uses a triangulation technique including observations, interviews, and documentation in the data collection. The result of this research elucidates that implementation of people’s nursery program policy in Bambalamotu Subdistrict, North Mamuju Regency in increasing land cover and people’s welfare is not optimal yet, based on the policy theory of George C Edward III, covering: communication which consists of transformation and information clarity are not satisfying yet, but the information consistency is fairly satisfying; the resources which consist of human resource quantity like top level executives is inadequate but the quality is adequate and human resource quality of low level executives is not adequate but the quantity is reasonably available, budget resource is inadequate, working facilities resource is adequate enough while the facilities of program final result in form of wood products industry are not available, and the information and authority resource are not optimal; Disposition related to support toward sustainability of program is not maximal; bureaucracy structure related to mechanisms implementation and bureaucracy structure are not maximal yet.